Orbital Cellulitis with Unilateral Rhinosinusitis in Adult - Febriani Endiyarti; Umar Said Dharmabakti; Yulia Aziza (Majalah Oftalmologi Indonesia, 2018)
Background : Orbital cellulitis is one of complication from rhinosinusitis. Although the prevalence in adult is less common than in children, the morbidity is higher. An appropriate treatment for this case should be given to avoid morbidity. Method : Serial cases of orbital cellulitis with unilateral sinusitis in Adult were reported in Dr.CiptoMangunkusumo Hospital. All cases occurred from December 2017-May 2018. Result : There were 4 cases reported. Range 26-57 years old. All cases had eyelid swelling, two cases had limitation eye movement, and two cases had visual deterioration. Ethmoid sinus was the most common sinus affected. All cases were treated with broad-spectrum antibiotic and metronidazole. Orbital decompression was performed in two cases. Conclusion: Appropriate treatments such as the use of systemic antibiotic and surgical is needed to decrease the morbidity.